2022
DOI: 10.3390/ijms23147537
|View full text |Cite
|
Sign up to set email alerts
|

Role of PsnWRKY70 in Regulatory Network Response to Infection with Alternaria alternata (Fr.) Keissl in Populus

Abstract: WRKY is an important complex family of transcription factors involved in plant immune responses. Among them, WRKY70 plays an important role in the process of the plant defense response to the invasion of pathogens. However, the defense mechanism of PsnWRKY70 is not clear in Populus nigra. In this study, we showed that PsnWRKY70-overexpression lines (OE) had fewer leaf blight symptoms than PsnWRKY70-repressing lines (RE). PsnWRKY70 activated MAP kinase cascade genes (PsnM2K4, PsnMPK3, PsnM3K18), calcium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For the structural genes in highly interacting gene clusters in the network, some have also been reported to be associated with stress resistance, such as the RLK gene involved in the LRR-RLK machinery mediating immune responses in Arabidopsis [ 38 ]. In poplar, LRR-RLK was also found to be involved in leaf blight resistance, which was regulated by PsnWRKY70 [ 16 ]. The HEL gene is a defense gene in plants that is associated with disease resistance in plants [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the structural genes in highly interacting gene clusters in the network, some have also been reported to be associated with stress resistance, such as the RLK gene involved in the LRR-RLK machinery mediating immune responses in Arabidopsis [ 38 ]. In poplar, LRR-RLK was also found to be involved in leaf blight resistance, which was regulated by PsnWRKY70 [ 16 ]. The HEL gene is a defense gene in plants that is associated with disease resistance in plants [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the initial exploration of regulatory mechanisms of leaf blight defense in poplar via transcriptome sequencing. Previous studies indicated that PsnWRKY70 -overexpressing transgenic plants displayed enhanced resistance to A. alternata in poplar by activating the genes in both pathogen-associated molecular pattern-triggered immunity (PTI) and effector-triggered immunity (ETI) [ 16 ]. In the study of Populus davidiana × Populus bollena against leaf blight, A. alternata was found to induce the differential expression of defense-related genes and ROS metabolism-related genes, and the hub gene PdbLOX2 could enhance the resistance to A. alternate in transgenic plants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ruiqi Wang identified four transcription factors related to disease resistance, including AtWRKY75, ANAC062, AtMYB23 and AtEBP, through the leaves of poplar (P. simonii × P. nigra) [39]. Further studies have shown that PsnWRKY70 enhances poplar resistance to Rhizoctonia allochthonii by activating genes related to pathogen-related molecular patterns (PTI) and effector-induced immunity (ETI) [40]. Exogenous application of sorbitol can further induce PsWRKY25 and PsCERK1 to improve the resistance of P. simonii to diseases [41].…”
Section: Research Progress Of P Simonii Genomicsmentioning
confidence: 99%
“…WRKY70 activates the expression of NPR1 and thus enhances PR expression, leading to the resistance of Arabidopsis to both biotrophic and hemibiotrophic pathogens but increasing plant susceptibility to necrotizing vegetative fungal pathogens ( Li et al., 2004 ; Li et al., 2006 ; Shim et al., 2013 ). In poplars, PsnWRKY70 enhance the resistance to A. alternata by activating genes involved in MAPK cascade and Ca 2+ signaling, other members of WRKYs , and LRR domain proteins ( Wang et al., 2022 ). Arabidopsis homolog transcripts WRKY70, WRKY51 and WRKY40 were strongly increased (more than 10-fold) in poplars after infection by Melampsora ( Miranda et al., 2007 ; Azaiez et al., 2009 ).…”
Section: Defense Responses Of Poplars To Fungal Pathogensmentioning
confidence: 99%
“…Poplars are predominantly distributed worldwide as model species of woody plants due to their rapid growth and stress tolerance. Populus is also hosts of a large variety of fungus ( Miranda et al., 2007 ; Wang et al., 2017a ; Wang et al., 2022 ). Fungal diseases not only affect the growth, but also cause large numbers of tree deaths and ecosystem degradation ( Eyles et al., 2010 ; Kovalchuk et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%